Postcolonial Europe - Jensen, Lars, author.
1 online resource (176 pages).
Keywords: "This book presents an overview of the direct and indirect ways in which Europe continues to be influenced by its entrenched postcolonial condition. Exploring the notion of postcolonial Europe as it characterizes a Europe caught at a number of crossroads, it considers the distinctly European features of a range of global crises by which Europe is beset, relating to migration, nationalism, internationalism, climate change and inequality. Linking these to the legacy of European hegemony during the era of high imperialism and the inability to come to terms with the region's increasingly provincialized status, the reversal of migrant flows following the implosion of European empires, and the dismantling of welfare societies initially made possible by the accumulation of wealth during colonialism, the author examines the gradual disintegration of the idea of the European collectivity and the erosion of the idea that Europe is a dispenser of privileged status. A wide-ranging study of Europe's crisis in its postcolonial era, this volume will appeal to scholars of critical sociology, political geography, cultural studies, anthropology, political science and history with interests in colonialism and postcolonialism"--